2022
DOI: 10.1038/s41598-021-03876-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of posterior pallial amygdala in mediating motor behaviors in pigeons

Abstract: The posterior pallial amygdala (PoA) is located on the basolateral caudal telencephalon, including the basal division of PoA (PoAb) and the compact division of PoA (PoAc). PoA plays a vital role in emotion regulation and is considered a part of the amygdala in birds. However, the regulatory functions responsible for motor behaviors and emotions between PoAb and PoAc are poorly understood. Therefore, we studied the structure and function of PoA by tract-tracing methods, constant current electrical stimulation, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Nevertheless, we have to admit that SMTS- pigeons, although they did not perform in more sessions, executed more pecks in total compared to the SR-group and thus we cannot completely exclude that pecking (physical) activity influenced the expression of receptors in the SMTS-group. However, we would see other brain structures like the basal ganglia, the cerebellum or parts of the pre-motor arcopallium/amygdala complex predominantly involved in such motor behavior ( Goodman et al, 1982 ; Yuan and Bottjer, 2020 ; Tian et al, 2022 ). Moreover, an earlier study of dopamine receptor expression after SR, SMTS and Delay-Matching-to-Sample training has shown that expression levels of receptors can change specifically according to different demands of cognitive tasks or learning components ( Herold et al, 2012 ).…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, we have to admit that SMTS- pigeons, although they did not perform in more sessions, executed more pecks in total compared to the SR-group and thus we cannot completely exclude that pecking (physical) activity influenced the expression of receptors in the SMTS-group. However, we would see other brain structures like the basal ganglia, the cerebellum or parts of the pre-motor arcopallium/amygdala complex predominantly involved in such motor behavior ( Goodman et al, 1982 ; Yuan and Bottjer, 2020 ; Tian et al, 2022 ). Moreover, an earlier study of dopamine receptor expression after SR, SMTS and Delay-Matching-to-Sample training has shown that expression levels of receptors can change specifically according to different demands of cognitive tasks or learning components ( Herold et al, 2012 ).…”
Section: Discussionmentioning
confidence: 97%
“…The second is the category targeted in the specific regions in the motivation and emotion system or pallium that are related to motion selection and decision-making to induce motives or virtual emotions for control. The typical regions include the dorsalis intermedius ventralis anterior (DIVA), the posterioramygdala (PoA), and the periaqueductal gray (PAG) [5,8,37,38]. Stimulation in these regions has successfully induced expected pigeon motion such as takeoff, hovering, left turn, right turn, and forward motion, bringing about a new era in the study of altering pigeon motor behavior using brain stimulation.…”
Section: Midbrain Motor Regionsmentioning
confidence: 99%
“…After that, the pigeons were fed in a single cage, and then electrical stimulation experiment would be carried out after 5-7 days of postoperative recovery. The details of the microelectrode implants procedure were described previously (Tian et al, 2022).…”
Section: Microelectrode Implantationmentioning
confidence: 99%
“…The responsive behaviors evoked by different stimulation intensity and different frequencies were recorded by using a SONY HDR-CX220 camcorder (Sony Corporation, Tokyo, Japan). The recorded behaviors were analyzed and defined following a standard mentioned in the previous work (Tian et al, 2022).…”
Section: Electrical Stimulation Protocolsmentioning
confidence: 99%